Profile of Entrants in Medical Residency Programs of National Cancer Institute José Alencar Gomes da Silva in the Period from 2013 to 2015 - Cavalcanti, Ismar Lima (2016)
Introduction: Knowing the profile of new students can serve as the basis for interventions in the teaching-learning process as well the administration of medical residency programs. Objective: To identify socioeconomic profiles, educational characteristics, motivations and expectations of new medical residents at the National Cancer Institute José Alencar Gomes da Silva (INCA), over the three years 2013-2015. Method: This is a descriptive study. The administrative data used were obtained from an optional and anonymous register offered at the time of enrollment in the programs. Results: The results showed that the majority of new residents are female, white, single and childless, live in the Southeast region, with the father as head of the family, have some kind of remunerated professional activity, want to live in INCA accommodation during the course, chose their specialty for personal reasons and for professional fulfillment, have an interest in scientific research and chose the INCA for the quality of care, clinical staff and infrastructure, as well as the quality of medical residency programs. Conclusion: It was possible to discover the profile of entrants through the investigated aspects. The quality of the actions developed and the interest in participating in scientific research at the institution influenced residents in choosing INCA for their qualification.